An empirical study on the consumer’s perception regarding the swot factors in indian banks - P, Manonmani; R, Haridas (Journal of Management and Science, 2013)
The stiff competition and advent of new technological innovations in banking system has made the industry highly challenging and vulnerable to sustain the completion. It forces the service providers to meet or exceed the target customers‘ satisfaction with quality of services expected by them. It becomes imperative to thoroughly scan the environment in which the firm survives. Hence the present study attempted to understand the consumers‘ perception regarding the SWOT factors in the banking industry. The study concludes that the most prioritized factors among Strength and weakness being employability and unstructured organization whereas opportunity and threat factors being customized services and criticisms respectively. To achieve the objectives a survey of 287 respondents were collected and analyzed through average score methods.